The Relationship between Religiosity and Student Mental Health in Malang - Sudrajat, Adi; Sufiyana, Atika Zuhrotus (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This study examines the impact of religiosity level on the mental health of students in Malang. This study aimed to determine the effect of religious levels on the mental health of students in Malang. This research methodology uses a quantitative approach. The collection technique used an online questionnaire administered through Google Forms to 347 student participants. The questionnaire included two main variables, namely, religiosity and mental health. The sample was selected using stratified random sampling to ensure representation from various universities and study programs. To ensure representation from multiple universities and study programs. This method helps minimize bias and ensures that various subgroups are proportionally represented. The data analysis of this study used several steps: descriptive statistical data analysis, correlational analysis, and regression analysis. The results of the analysis show that there is a significant positive relationship between the level of religiosity and students' mental health. Students with higher levels of religiosity tend to have better mental health. These results indicate the critical role of religiosity in improving the mental health of students; the research provides valuable scientific development contributions to efforts to improve mental health through a religious approach.